Cell cycle phase-specific death response of tobacco BY-2 cell line to cadmium treatment - Kuthanova, Andrea; Fischer, Lukas; Nick, Peter; Opatrny, Zdenek (Plant, cell & environment, 2008)
The character of programmed cell death (PCD) in plants differs in connection with the context, triggering factors and differentiation state of the target cells. To study the interconnections between cell cycle progression and cell death induction, we treated synchronized tobacco BY-2 cells with cadmium ions that represent a general abiotic stressor influencing both dividing and differentiated cells in planta. Cadmium induced massive cell death after application in all stages of the cell cycle; however, both the progression and the forms of the cell death differed pronouncedly. Apoptosis-like PCD induced by cadmium application in the S and G2 was characterized by pronounced internucleosomal DNA fragmentation. In contrast, application of cadmium in M and G1 phases was not accompanied by DNA cleavage, indicating suppression of autolysis and non-programmed character of the death. We interpret these results in the context of the situation in planta, where the induction of apoptosis-like PCD in the S and G2 phase might be connected with a need to preserve genetic integrity of dividing meristematic cells, whereas suppression of PCD response in differentiated cells (situated in G1/G0 phase) might help to avoid death of the whole plant, and thus enable initiation of the recovery and adaptation processes.
Keywords: Sulfates; buněčný cyklus; apoptóza; sírany; Cells, Cultured; Cell Survival; Mitotic Index; Nicotiana; viabilita buněk; Cadmium Compounds; DNA Fragmentation; sloučeniny kadmia; tabák; mitotický index; Apoptosis; kultivované buňky; fragmentace DNA; Cell Cycle